Differential epidemiology of Salmonella Typhi and Paratyphi A in Kathmandu, Nepal: a matched case control investigation in a highly endemic enteric fever setting. - Abhilasha Karkey; Corinne N Thompson; Nga Tran Vu Thieu; Sabina Dongol; Tu Le Thi Phuong; Phat Voong Vinh; Amit Arjyal; Laura B Martin; Simona Rondini; Jeremy J Farrar; Christiane Dolecek; Buddha Basnyat; et al. (Public Library of Science (PLoS), 2013)
BACKGROUND:Enteric fever, a systemic infection caused by the bacteria Salmonella Typhi and Salmonella Paratyphi A, is endemic in Kathmandu, Nepal. Previous work identified proximity to poor quality water sources as a community-level risk for infection. Here, we sought to examine individual-level risk factors related to hygiene and sanitation to improve our understanding of the epidemiology of enteric fever in this setting. METHODOLOGY AND PRINCIPAL FINDINGS:A matched case-control analysis was performed through enrollment of 103 blood culture positive enteric fever patients and 294 afebrile community-based age and gender-matched controls. A detailed questionnaire was administered to both cases and controls and the association between enteric fever infection and potential exposures were examined through conditional logistic regression. Several behavioral practices were identified as protective against infection with enteric fever, including water storage and hygienic habits. Additionally, we found that exposures related to poor water and socioeconomic status are more influential in the risk of infection with S. Typhi, whereas food consumption habits and migration play more of a role in risk of S. Paratyphi A infection. CONCLUSIONS AND SIGNIFICANCE:Our work suggests that S. Typhi and S. Paratyphi A follow different routes of infection in this highly endemic setting and that sustained exposure to both serovars probably leads to the development of passive immunity. In the absence of a polyvalent vaccine against S. Typhi and S. Paratyphi A, we advocate better systems for water treatment and storage, improvements in the quality of street food, and vaccination with currently available S. Typhi vaccines.